Aiskrim.My by Aysa / Nur Aisyah Likam - Likam, Nur Aisyah (2021)
AISKRIM.MY BY AYSA has been created and sell by Nur Aisyah Binti Likam and located at Kg Tengah Paya Redan, Pagoh, Muar Johor Malaysia. The founder of this business is Nur Aisyah itself and there have another three workers who are responsible as an accountant, promoter, and rider. They sell Aiskrim Malaysia with two main flavors, classic and premium flavors. Under classic flavor there have “asam bhoi, anggur, sarsi, laici and oren”. Premium flavor there have “choki choki, jagung susu, milo, sirap bandung and cumi”. There have different prices following the flavor, for classic flavor, the price is RM 0.80 and the premium flavor is RM1.00. The delivery cost starts from RM2 based on the area. The highest demand from the customer was Choki choki flavor. We also use the quality of milk. Customers can make orders through social media applications like WhatsApp and Facebook messenger. This business has their rider or customer also can self-pickup especially for those who stay around and do not want to spend on delivery’s cost. We also post any information that connecting to Aiskrim.My by Aysa. The mission or vision of this selling is to provide our customers with the enjoyment and ultimate “ aiskrim Malaysia” experience and motivate the entrepreneurial spirit